2019
DOI: 10.2298/gsgd1901029p
|View full text |Cite
|
Sign up to set email alerts
|

Changes in precipitation over the East Herzegovina region

Abstract: Changes in annual and seasonal precipitation over the East Herzegovina region in Bosnia and Herzegovina during the 1961-2016 periods were analyzed based on data sets of daily precipitation from 14 meteorological stations and rainfall gauges. The results show a downward trend in annual precipitation over the entire East Herzegovina region. Seasonal trend analysis showed that negative trends prevailed throughout the year, except in autumn season. Most prominent negative trends were registered in summer season th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
1
12
0
3
Order By: Relevance
“…Results showed that a downward trend in annual precipitation was present over the entire region (Popov, Gnjato, & Trbić, 2019a). A dry period started in the early 1980s and it is still going on (Popov et al, 2019a). Seasonal trend analysis showed that negative trends prevailed throughout the year (except in autumn) (Popov et al, 2019a).…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Results showed that a downward trend in annual precipitation was present over the entire region (Popov, Gnjato, & Trbić, 2019a). A dry period started in the early 1980s and it is still going on (Popov et al, 2019a). Seasonal trend analysis showed that negative trends prevailed throughout the year (except in autumn) (Popov et al, 2019a).…”
mentioning
confidence: 96%
“…of daily maximum and minimum temperatures, warm nights, warm days, warm spell duration, summer days and tropical days (Popov et al, 2018). Results showed that a downward trend in annual precipitation was present over the entire region (Popov, Gnjato, & Trbić, 2019a). A dry period started in the early 1980s and it is still going on (Popov et al, 2019a).…”
mentioning
confidence: 98%
See 3 more Smart Citations